D’une histoire des choses vues à l’histoire de l’image - Juliana Gendron (Frontière·s)
The eagle, omnipresent in the iconography of Roman power, was given a new lease of life with the emergence of the imperial cult. Alongside the image of the pyre, the image of the bird of prey was also a popular form of plastic commemoration during the consecration ceremony. It was during this ceremony, which was characterised by its spectacular staging and official sanction by the Senate, that the emperor symbolically received his apotheosis. According to Cassius Dion and Herodian, two Greek-speaking authors from the Severan era, a live eagle was placed at the summit of the immense consecratio pyre, after which it was released into the flames to symbolize the ascent of the deceased to Olympus. Nevertheless, despite the texts and images, there are several reasons to doubt that an eagle was present during the ceremony. It is unclear whether the images reflect a precise moment in the ceremony. It is necessary to ascertain whether the texts describe reality. The objective of this study is to compare iconographic and textual data, and to investigate the influence of figurative representations on the construction of narratives. To what extent did the iconographic representation of the eagle influence the literary descriptions of the ceremony? Did the authors base their accounts on what they had seen or on well-known images? In essence, the relationship between texts and images will be examined, not in terms of competition or the balancing of sources, but rather in terms of dialogue and even contamination.